Signal integrity from high speed to radiofrequency applications - Ndagijimana, Fabien (Focus series in digital signal and image processing, 2014)
Signal Integrity discusses the central theories involved in designing and testing radiofrequency and high-speed circuits. It addresses the various circuit levels of signal and propagation theory and the coexistence of high-speed wide band signals, radiofrequency signals, and supply circuits